Kuasa Patronase dan Klientelisme Kepala Desa Gunung Picung, Kecamatan Pamijahan, Kabupaten Bogor Pada Pilkada Serentak Kabupaten Bogor Tahun 2018. - Ranti Meidita Lestari (Epistemik: Indonesian Journal of Social and Political Science, 2021)
The practice of patronage politics and clintelism is still very much present in the political dynamics in Indonesia, even at the village level. This practice is usually marked by the control of political resources by a number of elites, especially the state elite. One of the practices of patronage and clientelism occurred during the simultaneous regional elections of Bogor Regency 2018. In which the success team of one of the candidates for the Bogor Regent used the Head of Gunung Picung Village, who is a local strongman in the area, to mobilize the masses in Gunung Picung Village to choose one of the candidates for the Bogor Regent. This patronage must be distributed through clientelism networks such as the success team that had been prepared long before the election which then consolidated with the Village Head to win the candidate for Regent. Then the relationship that occurs in the community, the Village Head mobilizes votes through money politics. From this it can also be said that the Village Head is making hegemonic efforts to the community through money politics. Money politics has given influence, awareness and interests of voters in determining their choices.